Perception of Family and Child in Different Turkish Cultures - Çetin, Asya; Özyürek, Arzu (Journal of History Culture and Art Research, 2023)
This study aims to determine the perception of family and child in Turkish origin people from different countries. The study group consisted of 107 students who volunteered to participate in the study from the Turkish countries and Turkish communities in the Asian continent, who continue their education in the departments at Karabuk University. A semi-structured interview form, which included 14 open-ended questions, was used to collect the data, which determined the views of the participants about the choice of spouse and marriage process, family roles and responsibilities, view of the child and kinship relations in their countries. The obtained data were analyzed with content analysis and reported. As a result of the study, it was concluded that the nuclear family structure is generally seen in Turkish families and the elders intervene in the choice of spouses of their children, the primary duty of women is to do all the housework, child care and education, and the man undertakes the economic responsibility of the family; the value attributed to children is high, all their needs are met, and the child is considered the joy and wealth of the family; there are usually 3-4 children in families, children are wanted one year after marriage, family elders want to have grandchildren immediately and sons are valued more; fidelity is important in marriages, fidelity is a must, infidelity is divorce etc. causing consequences; domestic violence can be encountered, women exposed to violence remain silent and men can use violence; It has been obtained that kinship relations are positive, strong and sincere.